Cascade energy transfer in dye-doped ternary polymer blend light-emitting diodes - Lee, TW; Park, OO; Cho, HN; Kim, YC (ELSEVIER SCIENCE SA, 2002)
We report the realization of efficient and color-variable organic electroluminescent (EL) devices which employ the cascade energy transfer in a dye-doped ternary polymer blend. Fluorene-based light-emitting polymers, poly(2,7-bis(p-stiryl)-9,9'-di-n-hexylfluorene sebacate) (PBSDHFS) and poly(9,9'-di-n-hexylfluorenediylvinylene-alt-1,4-phenylenevinylene) (PDHFPPV), and a laser dye, DCM were used for this study. Forster excitation energy transfer in the PBSDHFS/PDHFPPV (98w/2w), PDHFPPV/DCM (98w/2w), PBSDHFS/DCM (98w/2w), and PBSDHFS/PDHFPPV/DCM (98w/2w/2w) blend played an essential role in achieving color-tunability as well as high efficiency due to the reduced self-absorption loss and concentration quenching. The EL device made of the PBSDHFS/PDHFPPV/DCM (98w/2w/2w) blend showed the highest EL quantum efficiency (QE). We attribute this result to an effective carrier trapping capability of DCM as well as the excitation energy transfer. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: AMPLIFIED SPONTANEOUS EMISSION; CONJUGATED POLYMERS; ELECTROLUMINESCENCE; EFFICIENCY; FILMS